Bidirectional Photoresponse in Perovskite‐ZnO Heterostructure for Fully Optical‐Controlled Artificial Synapse. Issue 11 (24th March 2022) - Ge, Shuaipeng; Huang, Fengchang; He, Jiaqi; Xu, Zhangsheng; Sun, Zhenhua; Han, Xun; Wang, Chunfeng; Huang, Long‐Biao; Pan, Caofeng
Abstract: Compared with electrical synapses, optoelectronic synapses exhibit great potential for ultrafast computing and wireless communication in neuromorphic hardware with advantages of low crosstalk, high bandwidth, and low power consumption. However, due to the unidirectional photoresponse in most of optoelectronic synapses, the related researches still focus on the electrical stimulation of inhibitory behaviors. Herein, a synaptic device based on perovskite−ZnO heterostructure is prepared with the characteristic of bidirectional photoresponse and can realize both the potentiation and depression by ultraviolet (UV) and green light stimuli, respectively. Consecutive UV and green light stimuli for potentiation and depression reveal the reliability and repeatability of the fully optical‐controlled artificial synapse. A series of logic functions including "OR, " "AND, " "NOR, " and "NAND" has also been demonstrated in a fully‐optical pathway. This work not only offers an innovative architecture based on the perovskite single crystal and ZnO for fully optical‐controlled artificial synapse, but also represents a step toward optical wireless neuromorphic systems. Abstract : Limited by the unidirectional photoresponse in most optoelectronic synapses, the achievement of inhibitory behaviors still depends on electrical stimulation. Perovskite−ZnO heterostructure with bidirectional photoresponse is explored to emulate both the potentiation and depression by light illumination. Excitatory and inhibitory behaviors of the synapse and a series of logic functions have also been demonstrated in a fully‐optical pathway.